Long-term Forecast of the Dependence of the Economy of the Khanty-Mansi Autonomous Okrug-Ugra (Russia) on the Sectors of the Fuel and Energy Complex - Islamutdinov, Vadim Faruarovich; Kushnikov, Evgeniy Igorevich (International Journal of Energy Economics and Policy, 2020)
The purpose of study is to investigate long-term forecasting of the share of fuel and energy complex sectors in the economy of the Khanty-Mansi Autonomous Okrug-Ugra. 10 most significant economic industries (sectors) of the Khanty-Mansi Autonomous Okrug-Ugra were identified, with impact factors determined based on questionnaires and correlation analysis for each industry, as well as regression equations were derived and three forecast scenarios were calculated covering the period until 2028 were elaborated. Regardless of the development scenarios, the oil and gas industry will remain to be the mainstream one in the Khanty-Mansi Autonomous Okrug-Ugra within the next 10 years. All the rest of the industries will develop basically along with the dynamics of this predominant industry. This indicates the effect of the path dependence of the Khanty-Mansi Autonomous Okrug-Ugra economy. To boost the pace of the economic sectors development in the Khanty-Mansi Autonomous Okrug-Ugra, serious institutional changes are needed, which, with few exceptions, cannot be carried out at the regional level. Keywords: long-term forecast, fuel and energy complex, economic structure, energy, oil. JEL Classifications: Q32, Q43, Q48, R11, F13. DOI: https://doi.org/10.32479/ijeep.9081